A strategy for implementing genomics into nursing practice informed by three behaviour change theories. Issue 3 (30th May 2016) - Leach, Verity; Tonkin, Emma; Lancastle, Deborah; Kirk, Maggie
Abstract: Genomics is an ever increasing aspect of nursing practice, with focus being directed towards improving health. The authors present an implementation strategy for the incorporation of genomics into nursing practice within the UK, based on three behaviour change theories and the identification of individuals who are likely to provide support for change. Individuals identified as Opinion Leaders and Adopters of genomics illustrate how changes in behaviour might occur among the nursing profession. The core philosophy of the strategy is that genomic nurse Adopters and Opinion Leaders who have direct interaction with their peers in practice will be best placed to highlight the importance of genomics within the nursing role. The strategy discussed in this paper provides scope for continued nursing education and development of genomics within nursing practice on a larger scale. The recommendations might be of particular relevance for senior staff and management.